The impact of COVID-19 among Black women: evaluating perspectives and sources of information. Issue 1 (2nd January 2021) - Chandler, Rasheeta; Guillaume, Dominique; Parker, Andrea G.; Mack, Amber; Hamilton, Jill; Dorsey, Jemea; Hernandez, Natalie D.
ABSTRACT: Objectives: Coronavirus disease 2019 (COVID-19) has burgeoned into a pandemic that highlights the countless social and health disparities that have existed in Black communities within the United States for centuries. Recent epidemiological data show that Black communities are being disproportionately impacted by COVID-19, resulting in higher morbidity and mortality rates compared to other racial and ethnic groups. For Black women in particular, a long-standing history of systemic racism and marginalization has resulted in increased vulnerability and susceptibility to certain adverse health outcomes. Recent data show that COVID-19 knowledge rates among Black participants are low, and that Black women who become infected with COVID-19 have higher risks of complications and mortality compared to their non-Black counterparts. Given this data, there is a need to explore where and how Black women are obtaining information that pertains to COVID-19, along with the impacts that COVID-19 may be having on their daily lives. Design: We conducted interviews with 15 Black women who are clients at a community-based family service center to assess their understanding of COVID-19, determine how they were obtaining COVID-19 information, and evaluate the various impacts that COVID-19 was having on their lives. An initial codebook was developed based on the recorded interviews which included deductive and inductive codes. A thematic analysis of the data was then conducted using MaxQDA (Verbi Software), focusing on Black women's experiences related to COVID-19. Results: The majority of participants were using a combination of social media platforms and news sources to obtain information about COVID-19. Most participants (79%) expressed confusion, misunderstanding, and mistrust of the information that they were receiving about COVID-19. Conclusion: In addressing COVID-19-related health disparities within Black communities, it is imperative for trusted entities and organizations within Black communities to provide accurate and tailored information regarding this novel virus.